Analisis Kesetaraan Gender dan Upah dalam UMKM Kota Magelang: Peran, Akses, dan Upah - Nia Martha Tia; Danica Petrovski; Fernanda, Bagus Fernanda; Regita Dwi Wahyu Wulandari; Annisa Azalia; Grandis Salsabilla Ananta (Jurnal Studi Gender dan Anak, 2025)
This study aims to analyze the dynamics of gender inequality and the efforts to achieve economic equality within Micro, Small, and Medium Enterprises (MSMEs) in Magelang City, with a specific focus on the division of labor roles, access to core employment, and wage parity between men and women. Adopting the Gender and Development (GAD) framework, this research deeply explores how prevailing social norms, domestic power relations, and local micro-economic structures collectively influence women’s opportunities and economic participation. A descriptive qualitative method was employed, gathering primary data through in-depth interviews conducted across five diverse MSMEs: Anggrek Nambangan, Batik Rajah, Dhewi Laundry, Pabrik Tahu Trunan, and Cafe Utun & Mie Ayam Raya. The analysis of the findings is contextualized using Francine D. Blau’s theory on wage structure. The results indicate that women hold a substantial role, particularly in the service and family-based business sectors. However, their participation is still constrained by labor divisions based on gender stereotypes (e.g., assignment to light and repetitive tasks) and control stemming from domestic norms (particularly in the Dhewi Laundry case). Although there are claims of wage equality for similar work, the structural findings reveal that women’s access to strategic positions, formal managerial training, and economic mobility for career advancement remains highly limited, except in the case of Cafe Utun, which implements competence-based, gender-neutral recruitment and wages. This research concludes that women's empowerment within Magelang MSMEs is currently at the adaptive stage, yet to reach the transformative stage. Therefore, policy recommendations emphasize the necessity of inclusive structural interventions to improve women's access to capital, training, and core job opportunities.